Preparing Children for School in Fine Activities (Eurasian Journal of Media and Communications, 2021)
The Preschool Educational Institutional Program in Fine Arts and the Fine Arts Program in School provide for the development of children's aesthetic attitudes towards the environment, the development of creative abilities and artistic images. In pre-school education, the tasks necessary for successful schooling are solved. In the process of drawing, application, clay work, children develop aspects of thinking, such as analysis, synthesis, repetition, clarification